Mesorhizobium carmichaelinearum sp. nov., isolated from Carmichaelineae spp. root nodules. Issue 1 (20th November 2018) - De Meyer, Sofie E.; Andrews, Mitchell; James, Euan K.; Willems, Anne
Abstract : Five strains of Gram-stain-negative, rod-shaped bacteria were isolated from Carmichaelia and Montigena root nodules. Based on 16S rRNA gene phylogeny, they were shown to belong to the genus Mesorhizobium, and to be most closely related to Mesorhizobium jarvisii ATCC 33669 T (100–99.6 % sequence similarity), Mesorhizobium huakuii IAM 14158 T (99.9–99.6 %), Mesorhizobium japonicum MAFF303099 T (99.8–99.6 %) and Mesorhizobium erdmanii USDA 3471 T (99.8–99.5 %). Additionally, the strains formed distinct groups based on housekeeping gene analysis and were most closely related to M. jarvisii ATCC 33669 T (89.6–89.5 and 97.6–97.3 % sequence similarity for glnII and recA, respectively), M. erdmanii USDA 3471 T (94.3–94.0 and 94.9–94.1 %), M. japonicum MAFF303099 T (90.0–89.9 and 96.7–96.2 %) and M. huakuii IAM 14158 T (89.9–90.0 and 95.4–94.9 %). Chemotaxonomic data supported the assignment of the strains to the genus Mesorhizobium and DNA–DNA hybridizations, average nucleotide identity analysis, matrix-assisted laser desorption ionization time-of-flight MS analysis, physiological and biochemical tests differentiated them genotypically and phenotypically from their nearest neighbouring species. Therefore, these strains are considered to represent a novel species, for which the name Mesorhizobium carmichaelinearum sp. nov. is proposed. The type strain is ICMP 18942 T (=MonP1N1 T =LMG 28414 T ).